Rethinking Favela Governance: Nonviolent Politics in Rio de Janeiro's Gang Territories. (December 2018) - Fahlberg, Anjuli N.
Since the 1980s, when drug gangs became embedded in Rio de Janeiro's favelas, or poor urban neighborhoods, much has been written about the violent regimes that govern these spaces. This article argues that a nonviolent political regime run by activist residents also plays a critical role in favela governance by expanding the provision of services, promoting social development, fighting for their citizenship rights, and inserting favelas into political networks across the city. This claim is based on ethnographic fieldwork conducted between 2014 and 2017 in the City of God, one of Rio's most dangerous gang-controlled neighborhoods. Paradoxically, in activists' efforts to improve the neighborhood and fight for their rights, the nonviolent political regime in the City of God not only subverted violent politics but also helped to provide the conditions for its survival. Nevertheless, scholarship must account for nonviolent political actors in order to fully theorize favela governance.